Animated Video on the Topic of Plants and Their Functions in Science Learning - Suwastawan, I Gede Agus; Renda, Ndara Tanggu; Laba Jayanta, I Nyoman (MIMBAR PGSD Undiksha, 2022)
Teachers only use textbooks obtained from schools. Package books are considered less helpful for students because, without teacher guidance, students cannot understand the material well. This study aims to develop an animated video learning media on plant parts and their functions in science learning for fourth grade in elementary schools. This type of research is the development of the ADDIE model. The research subjects were two material experts and two media experts. The test subjects consisted of 2 teachers and three fourth-grade elementary school students. This study uses a questionnaire (questionnaire), interviews, observation, and documentation. This study uses a rating scale instrument. In this study, two data analysis techniques were used, namely qualitative descriptive analysis and quantitative descriptive analysis. The research results from learning material experts are 93.3% (Very Valid), and teaching media experts are 88.9% (Very Valid). The results of the practicality test from the teacher are 95.5% (very feasible), and the results of the student response test are 97.2% (very possible). It was concluded that animated videos were suitable for use in learning. This research implies that teachers in learning can use videos.